185k views
4 votes
Cos2A + cos2A cot2A = cot2A​

1 Answer

6 votes

cos(2A) + cos(2A) cot(2A) = cot(2A)

cos(2A) + cos(2A) cot(2A) - cot(2A) = 0

cot(2A) sin(2A) + cos(2A) cot(2A) - cot(2A) = 0

cot(2A) (sin(2A) + cos(2A) - 1) = 0

cot(2A) = 0 or sin(2A) + cos(2A) - 1 = 0

cot(2A) = 0 or sin(2A) + cos(2A) = 1

cot(2A) = 0 or sin(2A) cos(π/4) + cos(2A) sin(π/4) = 1/√2

cot(2A) = 0 or sin(2A + π/4) = 1/√2

[2A = cot⁻¹(0) + ] or

[2A + π/4 = sin⁻¹(1/√2) + 2 or 2A + π/4 = π - sin⁻¹(1/√2) + 2]

(where n is any integer)

[2A = π/2 + ] or

[2A + π/4 = π/4 + 2 or 2A + π/4 = 3π/4 + 2]

[A = π/4 + /2] or

[2A = 2 or 2A = π/2 + 2]

[A = π/4 + /2] or

[A = or A = π/4 + ]

A = (1 + 2n) π/4 or A = or A = π/4 +

User Ebbu Abraham
by
5.6k points